Distribution Evaluation of Tenofovir in the Breast Milk of Mothers With HBeAg-Positive Chronic HBV Infection After Treatment With Tenofovir Alafenamide and Tenofovir Disoproxil Fumarate by a Sensitive UPLC-MS/MS Method - Yang, Na; Zhou, Guanlun; Cheng, Xiaoliang; He, Jun; Chen, Yan; Chen, Chao; Li, Meijuan; Ge, Jiajia; Wang, Min; Zhang, Tianqi; Ge, Weihong; Zhu, Huaijun; et al. (Frontiers in Pharmacology, 2021)
Tenofovir alafenamide (TAF) is a novel prodrug of tenofovir (TFV) that has been approved for the treatment of chronic hepatitis B virus (HBV) infection. It has greater plasma stability and more favorable renal safety than TFV disoproxil fumarate (TDF), the first approved oral prodrug of TFV. However, the distribution of TFV in the breast milk of mothers treated with TAF is still unclear. In this study, sixteen participants with chronic HBV infection were enrolled and received antiretroviral therapy with 25 mg of TAF or 300 mg of TDF daily from 24 to 28 weeks of gestation until the 4th week postpartum. For the first time, the distribution of TFV in the breast milk of mothers with chronic HBV infection treated with TAF and its difference from TDF were evaluated by using a sensitive UPLC–MS/MS method. Chromatographic separation was achieved on a Waters ACQUITY UPLC BEH C18 column (1.7µm 2.1×100mm). Mass spectrometry analysis was performed in positive electrospray ionization mode and multiple reaction monitoring (MRM) conditions of transitions m/z 288.1→176.2 for TFV. This method was linear from 0.5 to 500 ng/mL. Surprisingly, on the third postpartum day, the median Cmax of TFV in the breast milk was much higher in the mothers treated with TAF (101.2 ng/mL) than TDF (21.6 ng/mL) at a similar Tmax of 4 h. Accordingly, the median AUC0-8 value was 755.6 ng·h/mL in the mothers taking TAF, which was at a 5-fold higher level than TDF. The concentration of TFV in the breast milk of mothers in both groups decreased with increasing lactation time. These data indicated that there was a relatively higher exposure of TFV in the breast milk of mothers taking TAF, despite the lower dosage compared to TDF. This study provides support for further evaluating the safety of breastfeeding after the administration of TAF and TDF.